Couter Radicalism in Central Java by Peace Education : The Central Java Regional Cyber Youth Peace Ambassador - Raundoh Tul Jannah; Endro Legowo; Achmed Sukendro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Based on data on the arrest of perpetrators of terrorism, radicalism, and extremism among Central Java youth through social media terror networks from 2003-2022 has increased. Security disturbances and non-military threats in the form of ideology can cause social conflicts that disturb religious, social, and political peace in real and virtual life. The Central Java NCTA Cyber Youth Peace Ambassador is present as an organization engaged in the issue of peace education through digital literacy skills to play an active role in filling social media with peace narratives, national insights, and alternative narratives in an effort to prevent conflict due to radicalism and terrorism for the sake of National Security in Java Middle. The purpose of this study is to analyze the actions and roles undertaken during 2017-2022.  Qualitative research methods, and constructivism research paradigm. The theories used are role theory, peace education, conflict, counter-propaganda for preventing radicalism, the concept of SISHANKAMRATA, and national security. The results of this study indicate that peace education efforts as counter-radicalism propaganda are carried out through two online and offline axles. NgrumPeace Program, Teng-Teng Crit, Content Sharing and Social Media (SKMS), Posters, Articles, Halte Rubric, SRAWUNG, Healthy DD, Audience, Gen Sae, and Company Profile. Efforts are not running optimally and must be optimized due to obstacles in constructing ideas, communication, and unclear legality of the organization. An active role is still not optimal, but it is very much needed as a concrete manifestation of youth involvement in efforts to maintain National Defense with the SISHANKAMRATA doctrine according to Law Number 3 of 2002 through digital and social literacy skills. Researchers recommend, further research is needed on the effectiveness of the role of Duta Damai, mapping the potential for radicalism among students including groups of people with disabilities in Central Java or other provinces.